A systematic review and meta-analysis of the association between arterial carbon dioxide tension and patient outcomes after cardiac arrest - Wang, Dandi; Li, Zhimao; Qin, Gerui; Cai, Liping; Zhang, Ting; Zhang, Hui; Liu, Yecheng; Zhu, Huadong (Frontiers in Medicine, 2025)
Background and aimsCurrent international guidelines suggest that normocapnia should be targeted during the resuscitation phase following cardiac arrest. However, some studies propose that therapeutic hypercapnia might be a potential strategy to enhance cerebral perfusion and improve patient outcomes after cardiac arrest. However, few studies have explored the association between arterial carbon dioxide tension and the prognosis of patients after cardiac arrest. This systematic review and meta-analysis aims to evaluate the influence of arterial carbon dioxide tension on the prognosis of patients after cardiac arrest.Data sourcesWe searched MEDLINE, Embase, and Cochrane CENTRAL to identify studies that evaluated the association between the partial pressure of arterial carbon dioxide and outcomes after cardiac arrest. The primary outcome was the neurological status at the end of the follow-up period. The secondary outcomes included short-, mid-, and long-term mortality. The meta-analysis was conducted if statistical heterogeneity was low.ResultsTwelve studies were included. Compared with normocapnia, hypercapnia was associated with lower in-hospital mortality (pooled OR 0.74, 95% CI 0.59–0.92). For neurological outcomes, hypercapnia was associated with less short favorable outcome (pooled OR 0.42, 95% CI 0.22–0.8).ConclusionAmong cardiac arrest patients, hypercapnia was associated with a reduction in in-hospital mortality and favorable neurological outcome compared to normocapnia.Systematic review registrationThis systematic review was registered with PROSPERO (ID: CRD42025644636).